Rethinking the social responsibilities of universities in the light of the COVID-19 pandemic (Comparative & International Education Series, 2021)
Universities should no longer be confined to their ivory tower. The ongoing revolution of higher education drives them to closely connect with outsiders to fulfill their vision, mission, and goals. The universities’ social responsibilities have become of utmost importance during the COVID-19 pandemic. In fact, the pandemic leads to the critical transformation of higher education worldwide. Multiple initiatives have been introduced to keep students engaged with their education. These solutions themselves, unfortunately, also lead to some social problems. The main contribution of this chapter, thus, is to provide reflection on multiple perspectives of universities social responsibilities (USR) pre-and post-COVID 19.How to cite this chapter:Thị, H. T., Nguyen, Q. D., & Tra, L-D. (2022). Rethinking the social responsibilities of universities in the light of the COVID-19 pandemic. In  R. Ammigan, R. Y. Chan, & K. Bista, (eds), COVID-19 and higher education in the global context: Exploring contemporary issues and challenges (pp. 25-38). STAR Scholars. https://starscholars.org/product/covid-19-and-higed/